Analysis of The Implementation of Carrier Aggregation Combinations That Occupy Non-Continuing Frequency Bands on The Existing LTE Network - Khalidya Igna Fillah; Sri Yusnita; Zurnawita Zurnawita; Yulindon Khaidir; Widya Andriani; Lin Fitri Alif Aisyah Aisyah (International Journal of Wireless And Multimedia Communications, 2026)
This study analyzes the effect of implementing Carrier Aggregation (CA) on non-adjacent frequency bands on LTE network performance in the Alai Parak Kopi area, Padang City, by measuring SINR parameters, uplink throughput, and downlink using the drive test method and TEMS application. The results show that CA affects the SINR value, with the highest value at a frequency of 1800 MHz (19.2 dB), followed by a combination of 1800 + 2300 MHz (18.5 dB), and 1800 + 2100 MHz (13.6 dB). CA also affects throughput, with the highest uplink at a combination of 1800 + 2300 MHz, while the highest downlink at 1800 MHz.